Empirical Examinations of the Information Sets of Economic Agents - Gottfries, Nils; Persson, Torsten (Quarterly Journal of Economics, 1988)
Nils Gottfries, Torsten Persson; Empirical Examinations of the Information Sets of Economic Agents*, The Quarterly Journal of Economics, Volume 103, Issue 1, 1